De l'intérêt d'une enquête quantitative sur les TIC(E) dans les collèges de Seine-Saint-Denis - Laurent Petit (Centre National d'Enseignement à Distance, 2014)
From a quantitative survey carried with college teachers in Seine-Saint-Denis in 2012, on behalf of the Conseil Général, the author shows that one can also take advantage of the survey to provide a scientific outlook on the issue of ICT at school: it reveals the contradictions and diversity of situations beyond the average values​​; beyond, it can be used to power the hypothesis of a "in-between" resulting from the clash of two conflicting logics. The hypotheses the questionnaire was built on, and that enabled that double reading are made explicit here. The ensuing interpretations are confronted to results from other surveys or studies on the same theme. It will have to be supported and precised later by others methods.